The Effects of Color Vision Deficiencies on Medical Professionals and Proposed Countermeasures. (September 2018) - Costedoat, Gregory; Palmer, Evan McHughes
Diagnosing various medical conditions and interpreting the results of colorimetric tests requires medical professionals to utilize color-based cues. However, those with a color vision deficiency (CVD) are at an increased risk of misdiagnosing patients and incorrectly interpreting the results of colorimetric tests. The most common CVDs afflicting medical professionals are deuteranomaly, deuteranopia, protanomaly, and protanopia, all of which reduce the ability to perceive a difference between green, yellow, orange, and red hues. For example, it has been found that medical professionals and students with a CVD have a decreased ability to detect blood in stool samples and are more likely to misread the results of colorimetric tests. In an effort to reduce these types of errors, potential countermeasures are explored, including screening for CVDs early on in medical school, implementing redundant coding principles for colorimetric medical tests, and designing efficient support systems for medical professionals with a CVD.